Climate sensitivity to land use changes over the city of Brussels - Cugnon, Gwenn; Caluwaerts, Steven; Duchêne, François; Hamdi, Rafiq; Termonia, Piet; Top, Sara; Vergauwen, Thomas; Van Schaeybroeck, Bert (Geographica Pannonica, 2019)
Prompted with the ongoing and projected climate change, a wide range of cities have committed, not only to mitigate greenhouse gas emissions but also to implement different climate change adaptation measures. These measures serve to ensure the wellbeing of the urban population. In practice, however, the planning of realistic adaptation measures is a complex process. Prior to starting such endeavor, it may therefore be useful to explore the maximum potential benefit that can be gained through adaptation measures. In this work, simple, extreme yet realistic adaptation measures are proposed in terms of changes in albedo and vegetation fraction. The impact of these land-use scenarios is explored by use of the land surface model SURFEX on the summer climate in terms of heat waves and the urban heat island for the city of Brussels. This is done for different periods in the future using the greenhouse gas scenario RCP8.5.
Keywords: climate change; adaptation; land use; urban climatology; scenarios